2017
DOI: 10.1007/978-3-662-54580-5_26
|View full text |Cite
|
Sign up to set email alerts
|

Lazy-CSeq 2.0: Combining Lazy Sequentialization with Abstract Interpretation

Abstract: Lazy sequentialization has emerged as one of the most effective techniques to find bugs in concurrent programs. However, the size of the shared global and thread-local state still poses a problem for further scaling. We therefore use abstract interpretation to minimize the representation of the concurrent program's state variables. More specifically, we run the Frama-C abstract interpretation tool over the sequentialized program output by Lazy-CSeq to compute over-approximating intervals for all (original) sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…More specifically, we run the Frama-C abstract interpretation tool over the programs constructed by Lazy-CSeq to compute overapproximating intervals for all (original) program variables and then exploit CBMC's bitvector support to reduce the number of bits required to represent these in the sequentialized program. We have implemented this approach on top of Lazy-CSeq and have demonstrated the effectiveness of this approach; it has performed very well in SV-COMP'17 competition, where it solved all tasks [26]. In this paper, in particular, we have further shown that it leads to large performance gains for very hard verification problems.…”
Section: Discussionmentioning
confidence: 79%
“…More specifically, we run the Frama-C abstract interpretation tool over the programs constructed by Lazy-CSeq to compute overapproximating intervals for all (original) program variables and then exploit CBMC's bitvector support to reduce the number of bits required to represent these in the sequentialized program. We have implemented this approach on top of Lazy-CSeq and have demonstrated the effectiveness of this approach; it has performed very well in SV-COMP'17 competition, where it solved all tasks [26]. In this paper, in particular, we have further shown that it leads to large performance gains for very hard verification problems.…”
Section: Discussionmentioning
confidence: 79%
“…The method recurs on all the instances where the timeout is reached. This method has the potential to take advantage of both the best available technologies for finding bugs, such as those based on BMC [17], [46], [47], [48], [49] and testing [38], [36], [22], and for proving absence of bugs, such as abstract interpretation [50], enhanced with the VERISMART approach.…”
Section: Discussionmentioning
confidence: 99%